Forest resource management based on GIS and Remote Sensing: Analysis from the Legislation and Scopus database (Texas Journal of Multidisciplinary Studies, 2025)
This paper explores the challenges and strategies for managing forest fires, with a focus on the role of human activity in causing and exacerbating wildfires. It highlights the significant damage caused by fires to forests, agricultural lands, and ecosystems, as well as the associated risks to human lives and livelihoods. The study also discusses the importance of preventive measures and effective fire management in forestry practices to mitigate the impacts of fires. Furthermore, the paper reviews recent trends in firerelated research and technological advancements, such as remote sensing and GIS, in monitoring and managing forest fires. The paper concludes by emphasizing the need for integrated strategies that address both prevention and response to forest fires.